Economic viability of integrated agricultural production systems with consortia during the pasture phase in Mato Grosso, Brazil - Souza, Sandra Maria Monteiro de Araújo; Gomes, Aguinaldo Rocha; Sabbag, Omar Jorge [UNESP]; Pacheco, Leandro Pereira; Wruck, Flávio de Jesus; Wingert, Gustavo; Macedo, Luís Otávio Bau; Silva, Laércio Santos [UNESP]; de Souza, Edicarlos Damacena (My University, 2023)
The particularities of Integrated Agricultural Production Systems (IAPS) influence the implementation costs and production profitability. However, there are few scientific approaches that seek to elucidate the total cost of IAPS, which aids decision making as to the most appropriate modality of IAPS to be installed. In this context, the purpose of this study was to (a) propose the application of the adequate costing method to IAPS, which allows an integrated economic-financial assessment and, (b) to assess the economic viability of IAPS with single pasture and consortiums under no-till in Mato Grosso. Between 2015 and 2017, four types of IAPS were conducted during the pasture phase and compared for economic viability. Based on the cash flow, the following economic viability indicators were calculated, Net Present Value (NPV), Benefit/Cost Index (BCI) and Internal Rate of Return (IRR). The absorption costing method allowed a comprehensive evaluation of IAPS production costs, through the apportionment criterion, and indirect costs were integrated to all production activities, enabling a full analysis of their costs. IAPS have different levels of profitability, depending on the grass used and the type of intercropping during the pasture phase. The overall net results between the systems, in the 15/16 and 16/17 harvests, ranged from R$ 701.81 to R$1,889.01, with the use of single pasture and R$1,435.86 to R$2,129.39 for the intercropped pastures. The consortium between Piatã and Cowpea presented the best economic indicators. The systems showed positive results with the ability to remunerate the investments made, especially when using the Piatã grass or with the use of intercropping between grasses and legumes in the pasture phase.
Keywords: Agricultural Credit.IAPS; Brazilian Savannah